Fetal Portal System Flowmetry and Intra-Amniotic Inflammation in Preterm Prelabor Rupture of Membranes - Musilova, Ivana; Spacek, Richard; Stranik, Jaroslav; Jacobsson, Bo; Kacerovsky, Marian (Fetal diagnosis and therapy, 2019)
OBJECTIVES: To determine the pulsatility index (PI) in the fetal splenic vein, the main portal vein, the left portal vein, and the ductus venosus with respect to the presence or absence of intra-amniotic inflammation (IAI) in preterm prelabor rupture of membranes (PPROM). METHOD: Women with singleton pregnancies and PPROM, ranging in gestational age from 22+0 to 36+6 weeks, were included. Amniotic fluid samples were obtained by transabdominal amniocentesis and the amniotic fluid level of interleukin-6 (IL-6) was assessed by a point-of-care test. Doppler examination of the selected veins was performed, and the PI was assessed. IAI was defined as amniotic fluid levels of IL-6 ≥745 pg/mL. RESULTS: In total, 42 women were included. Fetuses with IAI compared with those without IAI exhibited a higher PI in the splenic vein (p = 0.005) and the main portal vein (p = 0.05). No differences were observed in the left portal vein PI (p = 0.36) and the ductus venosus PI (p = 0.98). CONCLUSION: IAI was associated with increased fetal splenic vein PI and main portal vein PI in PPROM. The absence of changes in the left portal vein PI and ductus venosus PI supports the local cause of the finding.
Keywords: gestační stáří; dospělí; chorioamnionitida; Chorioamnionitis; Female; Splenic Vein; Doppler examination; ultrasonografie dopplerovská barevná; Gestational Age; Adult; ženské pohlaví; vena portae; lidé; těhotenství; předčasná porodní činnost; Portal Vein; Interleukin-6; Amniotic fluid; rychlost toku krve; Blood Flow Velocity; Ultrasonography, Prenatal; prospektivní studie; Pulsatile Flow; Prospective Studies; Amniotic Fluid; plodová voda; Ultrasonography, Doppler, Color; interleukin-6; vena lienalis; Ultrasound; Liver Circulation; Obstetric Labor, Premature; jaterní oběh; pulzatilní průtok; Pregnancy; ultrasonografie prenatální; Intra-amniotic infection; Splenic vein; Humans